Regulation of PDE5 expression in normal prostate, benign prostatic hyperplasia, and adenocarcinoma. (21st August 2019) - Bisegna, C.; Gravina, G. L.; Pierconti, F.; Martini, M.; Larocca, L.; Rossi, P.; Grimaldi, P.; Dolci, S.; Di Stasi, S.; Jannini, E. A.
Abstract: Background: Type 5 phosphodiesterase (PDE5) expression in the normal and pathological prostate is controversial. Objectives: This study aimed at identifying the cell type/s, if any, expressing PDE5 in human healthy or pathological prostate sections in order to further validate the rationale of PDE5 inhibitor (PDE5i) treatment of benign prostatic hyperplasia (BPH) and their safety in the treatment of erectile dysfunction following prostate cancer (PCa) surgery. Materials and methods: By immunohistochemical analysis, we studied PDE5 expression in tissue microarrays containing sections obtained from healthy, BPH, and PCa samples. Results: Our results showed that PDE5 is barely expressed in the epithelial or stromal compartment of normal human prostates, but it is highly expressed in the stromal compartment of BPH sections. We also found that a low but significant number of PCa samples (22%) expressed PDE5 in the epithelial cancer cells but not in stromal cells and that such expression was not correlated with the tumor aggressiveness, according to their Gleason score. Discussion and conclusion: PDE5 overexpression in the stromal compartment of BPH samples supports the rationale of PDE5 as a target in lower urinary tract symptoms of BPH. PDE5 expression in a significant percentage of PCa samples but the lack of correlation with the Gleason score suggests that this enzyme is not correlated with tumor aggressiveness; however, a role of PDE5 in the minimal residual disease of PCa cannot be excluded.